Pengaruh Umpan Balik Anggaran dan Evaluasi Anggaran Terhadap Kinerja SKPA Pemerintah Provinsi Aceh - Jumiati Jumiati; Islahuddin Islahuddin (Jurnal Telaah dan Riset Akuntansi, 2017)
This study aimed to examine the effect of budget feedback and budget evaluation both simultaneously and partially on the SKPA performance of the Aceh Provincial Government. The unit of analysis of this researchwere all institutions that exist in the Government of Aceh as much as 40 SKPA, while the research unit were the Head of Division and Head of sub-section, because all members of the population made respondents, then this study used the census method. Sources of data in this study used primary data, where the results of questionnaires obtained from respondents research. While the technique of collecting research data was done by documentation technique of collecting research questionnaires. The analysis method used was Multiple Linear Regression Analysis. The results showed that budgetary feedback and budget evaluation both simultaneously and partially affect the performance SKPA Provincial Government of Aceh.KEYWORDS : budget feedback, budget evaluation, performance